Enhancing the quality of tuberculosis care in a high-prevalence area of West Java, Indonesia: A comparative study between public and private hospitals - Dewi, Inaz K.; Hairi, Farizah M.; Andriani, Helen (Narra J, 2025)
Despite the World Health Organization’s (WHO) ambitious goal of eradicating tuberculosis (TB) by 2035, the three key indicators of the End TB Strategy remain unmet. Improving the quality of care is essential to achieving better health outcomes in Indonesia, where both public and private hospitals play a pivotal role in strengthening TB services. The aim of this study was to evaluate the quality of TB care in public and private hospitals in Karawang Regency, a district with the fifth highest TB prevalence in West Java, Indonesia. A mixed-methods approach was employed, using an evaluation framework that integrated the High-Quality Health System (HQHS) model and the Quality of Tuberculosis Service Assessment (QTSA) tool. Quantitative data were collected using a modified QTSA questionnaire administered to patients, while qualitative primary data were obtained through in-depth interviews with stakeholders and healthcare providers. Secondary qualitative data were sourced from patient visit records and TB control reports. The findings indicated that low treatment success rates were associated with increased patient loss to follow-up, inadequate evaluation, patient mortality, and dissatisfaction, which were largely driven by deficiencies in foundational elements and suboptimal treatment processes, including budgeting, policy dissemination, and the functioning of internal and external networks. Positive patient experiences and access to follow-up care significantly influenced patient satisfaction. Strengthening the foundational components of the TB health system and adopting a sustainable, integrated treatment approach are critical to improving treatment success rates, clinical outcomes, and patient satisfaction.